General Characteristics of Thinking as a Mental Process - Dilbar, Mukhamedova; ogli, Xujamshukurov Tolibnazar Rashid (European Journal of Life Safety and Stability (2660-9630), 2023)
Thinking is the reflection in our mind of the most important connections and relationships between things and events. A person studies the environment (things, events, people) and himself in order to perform various activities and achieve certain socially and personally important goals by influencing these objects. Intuition, perception and imagination, in cooperation with involuntary attention and visual memory, provide a person with information about specific objects and their directly studied properties. These forms of mental reflection are the emotional basis of human knowledge of objective reality. But knowledge of individual bodies and real-world phenomena is not enough to find answers to three important questions that arise when solving any practical task. These questions consist of: "what can be done in a given situation, how can it be done, and what will be produced as a result of this action?"Thinking helps us to find answers to these questions. First of all, thinking is a mental process of high-level cognition. The essence of this process is the active creative reflection and change of reality by a person.